2017
DOI: 10.1007/s10967-017-5383-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction of Cu, Mo, V, and U from leach solutions of copper ore and flotation tailings

Abstract: Flotation tailings from copper production are deposits of copper and other valuable metals, such as Mo, V and U. New hydrometallurgical technologies are more economical and open up new possibilities for metal recovery. This work presents results of the study on the extraction of copper by mixed extractant consisting p-toluidine dissolved in toluene. The possibility of simultaneous liquid–liquid extraction of molybdenum and vanadium was examined. D2EHPA solutions was used as extractant, and recovery of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In general, fine-grained sulfides react faster than coarse-grained sulfides due to an exponential increase in their surface areas [64]. The mineral processing of Cu ores requires grinding of the ore prior to flotation and extraction [65], and the historical tailings in Repparfjorden contain mostly silt-sized sulfide particles (mean 7.6 to 11.6 µm; Appendix C). In addition to sulfides, the tailings contain silty silicates and rare carbonates that may buffer the system and prevent the formation of ARD.…”
Section: Physicochemical Factors That Control the Oxidation Of Sulfidesmentioning
confidence: 99%
“…In general, fine-grained sulfides react faster than coarse-grained sulfides due to an exponential increase in their surface areas [64]. The mineral processing of Cu ores requires grinding of the ore prior to flotation and extraction [65], and the historical tailings in Repparfjorden contain mostly silt-sized sulfide particles (mean 7.6 to 11.6 µm; Appendix C). In addition to sulfides, the tailings contain silty silicates and rare carbonates that may buffer the system and prevent the formation of ARD.…”
Section: Physicochemical Factors That Control the Oxidation Of Sulfidesmentioning
confidence: 99%
“…In the next stages, flotation allows extracting copper particles from the fine ore dust. In this way the concentrate is obtained, that after drying is transferred to smelting plants [ 4 ]. Process flow is visualized in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the studies on recycling Cu from the solid wastes using MFCs have been scarcely reported [42][43][44][45]. Moreover, the water pollution and ecological destruction caused by the traditional hydrometallurgical methods have plagued the development in the mining industry [40,[46][47][48][49]. In this study, the bioleaching technique and a dual-chamber MFC were assembled to achieve the extraction and recovery of Cu from the secondary copper tailings at same time.…”
Section: Introductionmentioning
confidence: 99%